2015
DOI: 10.1292/jvms.15-0008
|View full text |Cite
|
Sign up to set email alerts
|

The effects analysis of two neonicotinoid insecticides on <i>in vitro</i> maturation of porcine oocytes using hanging drop monoculture method

Abstract: Acetamiprid (ACE) and imidacroprid (IMI) are known neonicotinoid insecticides with strong affinities for the insect-selective nicotinic acetylcholine receptor. These provide insect control by hyperstimulating insect nerves and are used for agricultural pest management. However, it has also been reported that ACE and IMI affect mammalian reproductive function. We determined the effects of ACE and IMI on the in vitro maturation of porcine oocytes. Significant decreases in nuclear maturation rates were observed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Importantly, significant alternations of genes associated with oocyte meiosis ( ccnb1 and cdc20 ) were observed in F1 in this research. Published studies report that IMI is detrimental to sperm function or oocyte maturation, fertilization, and subsequent development in bees, mice, and porcine. In addition, steroid biosynthesis was significantly enriched in the THM groups in F1 generation, which were consistent with the data from the gonads in F0 generations. Interestingly, paternal/maternal exposure to IMI and THM all decreased the levels of T and E2 in F1 generations.…”
Section: Discussionmentioning
confidence: 80%
“…Importantly, significant alternations of genes associated with oocyte meiosis ( ccnb1 and cdc20 ) were observed in F1 in this research. Published studies report that IMI is detrimental to sperm function or oocyte maturation, fertilization, and subsequent development in bees, mice, and porcine. In addition, steroid biosynthesis was significantly enriched in the THM groups in F1 generation, which were consistent with the data from the gonads in F0 generations. Interestingly, paternal/maternal exposure to IMI and THM all decreased the levels of T and E2 in F1 generations.…”
Section: Discussionmentioning
confidence: 80%
“…However, concentrations of 30 ppm and 100 ppm significantly reduced oocyte maturation. Although the exact mode of action of ACP on oocyte maturation is unknown, occurrence of increased lipid peroxidation and decreased antioxidant factors including glutathione and super oxidase, catalase, glutathione peroxidase has been described ( Ishikawa et al ., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested that the main mechanisms for ACP-induced toxicity include increased oxidative stress, decreased activity of antioxidant systems that play a protective role in the body (ROS), and increased lipid peroxidation of membranes. Ishikawa et al (2015) evaluated the effect of ACP on the maturation of porcine oocytes in a laboratory. The results showed that oocyte nucleus maturation in the group given ACP at a concentration of 10 ppm was not significantly different from controls.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of ACE and imidacloprid on porcine oocyte maturation in vitro have been reported previously. Irregular chromosomes were observed in the ACE-or imidacloprid-exposed groups and nuclear maturation rates were significantly reduced (Ishikawa et al, 2015). Formate insecticides are commonly used.…”
Section: Pesticidesmentioning
confidence: 99%